Response of Organic Fertilizer Formulation on the Growth and Production of Purple Eggplant (Solanum melongena L) - Murni, Maria Gardiana; Herawati, Jajuk; Thohiron, Mochamad (Journal of Applied Plant Technology, 2025)
This study examines the effect of organic fertilizer formulations on the growth and yield of purple eggplant (Solanum melongena L.). Conducted at the Bhakti Bapak Emak Islamic Boarding School, Jombang, over three months (May–August 2024), the research used a Randomized Block Design with five treatments and four replications: T0 = NPK 2.57 g (control), T1 = NPK 2.57 g + 4 tons of granular organic fertilizer (50.2 g/ha), T2 = NPK 2.57 g + 4 tons of crumb organic fertilizer (50.2 g/ha), T3 = NPK 2.57 g + 6 tons of granular organic fertilizer (75.4 g/ha), and T4 = NPK 2.57 g + 6 tons of crumb organic fertilizer (75.4 g/ha). The results showed that granular and crumb organic fertilizers significantly improved growth and yield parameters. Significant differences were observed in plant height (35–42 days after planting, DAP), leaf count (42 DAP), fruit diameter, flowering age, fruit length, and fruit volume, with the best performance at T3 (6 tons granular).